Response of temperate forest ecosystem services to rainfall: A case study in the forest nature reserves of northern China - Liang, Mei; Han, Tian; Ma, Jinfeng; Li, Ruonan; Yang, Yanzheng; Qiu, Xiao; Sun, Hailian; Zheng, Hua (Frontiers in Ecology and Evolution, 2023)
In the context of global climate change, temperate forests in climate-sensitive areas are inevitably affected. To deepen the understanding of the impact on precipitation changes into the relationship between key ecosystem services (ESs), this study selected net primary productivity (NPP), soil conservation (SC) and water yield (WY) of temperate forest in northern China as objects, and the Spearman correlation test and redundancy analysis were applied to analyze the response of ESs relationship to precipitation gradient. The results show that precipitation is the meteorological factor with the greatest impact (contribution 21.2%, p<0.01) on ESs and their relationships in temperate forests. The 600-700 mm precipitation gradient is the key turning point in the change of ESs relationship of WY with NPP and SC. This indicates that attention should be paid to the spatial variation of the 600-700 mm precipitation region in the future warm-wet in northern China, which should be used as a dividing line of forest management and policy development. Based on the results, future restoration projects in northern temperate forest should focus on (1) in areas with less than 600-700 mm of precipitation, attention should be paid to the selection of tree species for afforestation to maintain regional water balance; (2) in areas with more than 700 mm of precipitation, soil and water conservation projects need to be planned, especially in mountainous area. The research can not only support the management of temperate forest ecosystems in northern China, but also provide reference to other forest ecosystems to cope with climate change.